Recent Advancements on Design and Development of Multi Drop Auto-Walk - Swaminathan, G.; Kumar, S. D.; Mathivanan, A. (Advanced Aspects of Engineering Research Vol. 3, 2021)
At present environment, especially in the urban cities, peoples are very busy and moving continuously and rapidly. With the advancement in technologies, there is a huge opportunity to full fill this people flow experience. Autowalk which is also called as walkalator or movelator is a device used as a mode for transporting the peoples horizontally or laterally from one point to another. The proposed device consists of a pulley with belt arrangement or can be a pallet type of arrangement which is being driven by a motor. Autowalk available in the market today can only transport the people from one point to another, however, for the place where people has to move in a wide spread direction, rather than the point to point there is a need for some devices or some modifications in the existing setup to satisfy those needs. No doubt the development and advancement in technology and the simultaneous growth in people modern lifestyle always give a way for a demand in solution for a better lifestyle. In this multidrop autowalk the people flow traffic is optimized by providing the sub-platform which moves simultaneously along with the main lane. This multidrop autowalk can be widely used in departmental stores, airports, shopping malls, theme park, exhibitions, etc. And this attempt will give be a mark on development path meeting such need.